The Relationship between Organizational Commitment and Innovative Work Behavior in MTSN X - Amalia, Maulida; Budiani, Meita Santi (Universitas Negeri Surabaya, 2023)
This study aims to determine the relationship between organizational commitment and innovative work behavior among teachers at the Foundation x. The research method used in this study is quantitative. The sample in this study was 78 people. Data collection techniques using techniquespurposive sampling. The research instrument used was a scale of organizational commitment and a scale of innovative work behavior. Data analysis using correlationpearson product moment with the help ofsoftware IBM SPSS 26 for windows, which shows the results of a positive and significant relationship between organizational commitment and innovative work behavior with a significance value of 0.000 (p <0.05). It is also known that the correlation coefficient value is 0.705 which is included in the high and one-way category. This study shows the results of a positive relationship and significant relationship between organizational commitment and innovative work behavior among teachers at MTSN X.